Identification of Elementary School Students' Physical Fitness Level in Sugihwaras Districts Bojonegoro - Priadana, Benny Widya; Suwandi, Edi (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2023)
The purpose of this study was to determine the physical fitness condition of elementary school (SD) students in the Sugihwaras sub-district, Bojonegoro district. The research method used is a survey. A total of 112 (56 males and 56 females) were the subjects of this study. Data analysis used descriptive statistics and percentages. The results showed that the muscular and cardiovascular fitness of male students were better than female students. However, the cardiovascular fitness of both male and female students was mostly in the beginner and developing levels. Therefore, schools, stakeholders, and physical education teachers need to better facilitate students so that they can be physically active in their spare time or at rest, take regular physical fitness measurements and create meaningful learning combined with innovative fitness-oriented games.